Pengurusan Program Kitar Semula Di Daerah Kerian, Perak Darul Ridzuan - Mohamed Nordin, Fadhlia (Universiti Sains Malaysia, 2006)
Amount of solid waste is increasing hand in hand with increasing in technologies due to the use of packaging items such as foods or others equipment like cloths, daily requirement and so on. Generating of solid waste not only increases composition of waste in landfill but it also contributes negative aspects such as pollutions. Therefore recycling practice is given more priority to minimize the solid waste and reduce the environment pollution. This study is to ensure the level of effectiveness in recycling program that has been conducted in the district of Kerian, Perak. Everyday, 120 tons of solid wastes are generated in Kerian, Perak with a population 152,650. Besides this, this study is to see whether the information by the media were convey to the community and to ensure community awareness about the significance of recycling program by analyzing the statistics of recycle items in Kerian, Perak. The result showed the recycle practicing is still not up to the required level even the information were convey to the public is grade. Suggestion given by the respondent is to increase the prices of recycle items to attract the community in joining the program.